The effect of national culture on the choice between licensing and direct foreign investment - Shane, Scott (Strategic Management Journal, 1994)
Abstract This paper argues that national differences in levels of trust impact perceptions of transactions costs and thereby influence the desirability of internalization and the choice of foreign market entry mode. The paper tests this framework on industry level data from the United States Commerce Department's Benchmark Survey of operations of U.S. ‐based manufacturing multinational corporations in 1977 and 1982, and shows that cultural differences in trust do influence perceptions of transaction costs and the preference for direct foreign investment across countries.